Type 2 Diabetes, Atrial Fibrillation, and Direct Oral Anticoagulation - Dana Prídavková; Matej Samoš; Tomáš Bolek; Ingrid Škorňová; Jana Žolková; Peter Kubisz; Ján Staško; Marián Mokáň (Journal of Diabetes Research)
Type 2 diabetes (T2D) is an independent risk factor of stroke and systemic embolism in patients with atrial fibrillation (AF), and T2D patients with AF-associated stroke seem to have worse clinical outcome and higher risk of unfavorable clinical course compared to individuals without this metabolic disorder. Long-term anticoagulation is indicated in majority of T2D patients with AF to prevent adverse AF-associated embolic events. Direct oral anticoagulants (DOACs), direct oral thrombin inhibitor dabigatran, and direct oral factor Xa inhibitors, rivaroxaban, apixaban, and edoxaban, have emerged as a preferred choice for long-term prevention of stroke in AF patients offering potent and predictable anticoagulation and a favorable pharmacology with low risk of interactions. This article reviews the current data regarding the use of DOACs in individuals with T2D and AF.